Cosméticos artesanais: uma abordagem para o ensino médio em química - Klein, Vanessa (2022)
Chemistry is perceived, by students, as a highly complex and difficult subject, which demands a great degree of abstraction in some of its contents. Such impasses often result in difficulty in understanding some concepts, leading to demotivation, disinterest and learning issues. Considered by students as one of most complicated contents in high school, organic chemistry has the responsibility of amplifying the students’ perspective towards life, the planet and its existing components, such as food, clothes, medicines, transportation and cosmetics. Cosmetics are utilized by the majority of global population and, as such, can be easily found in our daily life, becoming an accessible example of products that are directly associated to different scientific concepts approached in high school chemistry. Given that fact, the present research aims to promote a wider knowledge on the subject “cosmetics” through workshops on handmade cosmetics. Beyond that, the workshop aims to provide students with an alternative source of income, considering that the skills learned can be reproduced in their own houses and commercialized afterwards. The workshops were developed with senior high school students in the following schools: Escola Estadual de Educação Básica Prof.ª Margarida Lopes, Instituto Estadual de Educação João Neves da Fontoura and Instituto Estadual Couto de Magalhães, located respectively in Santa Maria/RS, Cachoeira do Sul/RS and Arroio dos Ratos/RS. These activities were performed in the following months: September and October of 2019 and May and June of 2022, during the afternoon in the schools’ science labs. The target audience were a total of 21 students between 16 and 19 years old. The activities could be classified as thematic workshops, as according to Marcondes et al. (2007), in thematic workshops the activities are based on experiments, interconnected from a generator topic. Six different activities were performed and carried out the following themes: (1) Developing soap; (2) Developing liquid soap; (3) Developing shampoo; (4) Developing hand-moisturizing cream; (5) Developing air freshener and fragrant sachets; (6) Toothpaste substance analysis, the latter being conducted only in 2019. The students were incited to perform the activities and later discuss and comment their learnings, attempting to relate them to classroom chemistry. Through the workshops, there was a noticeable relevant learning on the part of the students, because they were highly interested by the artisanship of the cosmetics and so they could relate the workshop topics with chemistry and their daily life. The workshops provide a connection between theoretical chemistry and real attainable work that may become a source of income to the students. In that sense, it is of great importance to approach day-to-day topics in classroom, once this connection instigate the students to seek knowledge and become more critic and active members of society